Development and construction of a novel Bacillus subtilis autoinducible extracellular expression system based on a LuxI/R device - Bin Wang; Keyi Wang; Xiuyue Zhao; Zemin Fang; Yanyan Zhao; Yulu Fang; Yazhong Xiao; Dongbang Yao (Microbial Cell Factories)
Abstract Background Microbial chassis expression systems are valuable tools in biotechnology and synthetic biology, and Bacillus subtilis is an important industrial microbial chassis. Quorum sensing (QS)-based dynamic regulation is widely used to automatically activate gene expression in response to changes in cell density. The main bottleneck currently limiting the use of exogenous QS systems in B. subtilis for efficient autoinducible extracellular expression of recombinant proteins is their low level of autoinducible expression. Results A novel B. subtilis autoinducible extracellular expression system based on the LuxI/R-type QS system (lux system) of Vibrio fischeri was developed in which the autoinducible expression of the lux system was enhanced by engineering the sensing module and response module promoters. By engineering the sensing module promoter SP luxI core region (− 10 and − 35 elements) and critical region (UP and spacer elements), and the response module promoter RP luxIR6 core region and lux box copy number in the original LuxI/R device (S0-R0), the high-expression Sc-R2 construct was obtained. After shake flask and 3-L fermenter fermentation, the extracellular amylase activity obtained with Sc-R2 was 2.7- and 3.1-fold greater, respectively, than that obtained with the well-characterized promoter P veg . Sc-R2 achieved 2.6-fold greater extracellular activity than S0-R0 when either levansucrase or invertase was used as a reporter protein. Overall, the B. subtilis autoinducible extracellular expression system developed in this study showed good generalizability and application potential for industrial-scale fermentation. Conclusions To our knowledge, this is the first study to report enhanced autoinducible expression of the lux system in B. subtilis by engineering the sensing module promoter SP luxI sequence and the lux box copy number of the response module promoter RP luxIR6 . This study further expands the application potential of the B. subtilis expression system in synthetic biology.